The “love of the homeland”: representations of civism on the Despertar - Dewes, Elisangela Cândido da Silva; Souza, José Edimar de (Faculdade de Educação/Universidade Estadual de Campinas, 2020)
This article is a fragment of a study developed around the Jornal Despertar, a pedagogical form produced by the Board of Public Instruction of the city of Caxias do Sul, between 1947 and 1954. The study sought to analyze the meanings constructed by the readers of the journal, from of the representations present in different sections of the newspaper. In addition, it sought to understand how the guidelines influenced and transformed the practices of the inhabitants of rural areas. As a theoretical contribution, concepts from Cultural History were used and as a methodology document analysis of fifty-three editions of the journal. The investigation resulted in the understanding that municipal administration used the periodical as a means to strengthen representations about an archetype of “Brazilian citizen” and, in this way, to influence the rural community to civic behavior.